Voice Controlled DC Motor System Using IoT Monitoring: Sistem Motor DC yang Dikendalikan Suara dengan Pemantauan IoT - Imron Muhammad Triaji; Shazana Dhiya Ayuni (Indonesian Journal of Innovation Studies, 2025)
General Background DC motors are widely used in industrial and household applications requiring precise and flexible speed control. Specific Background Recent advancements in Internet of Things and voice recognition technologies enable more intuitive and remote-based control systems. Knowledge Gap Conventional DC motor control systems are generally limited to manual or application-based interfaces without integrated voice command features. Aims This study aims to design and implement a DC motor control system using voice commands integrated with IoT-based monitoring. Results The system utilizes a microcontroller, PWM method, and voice recognition module to control motor speed, where voice inputs are successfully translated into motor responses and monitored through an IoT platform. Novelty The integration of voice command control with IoT-based monitoring provides a more interactive and accessible approach for DC motor operation. Implications This system offers a practical solution for remote and user-friendly motor control, supporting the development of smart automation systems in various applications. Keywords: Voice Recognition, Internet of Things, DC Motor Control, PWM, Smart System Key Findings Highlights Voice commands are successfully converted into motor speed adjustments Monitoring system enables real time observation through network connectivity Integrated control approach simplifies user interaction with hardware systems